The Impact Of Absorptive Capacity On Banking Performance:An Analysis Of The Mediating Effects Of Marketing Mix And Innovation - Irawan R D Budianto; Hadita Hadita; Fajri Fajri (International Journal of Management Research and Economics, 2023)
This paper conceptually analysed the special issue briefly reviews about absorptive capacity. Based on a systematic literature review, the paper discusses the Impact of Absorptive Capacity on Banking Performance in Indonesia. The paper also explains the mediating effect of marketing mix and innovation on the performance of banks in Indonesia which shows that the mediation of marketing mix and innovation has a positive effect on the impact of absorptive capacity on bank performance. The paper offers a definition of absorptive capacity for strategic management discipline, constructs a conceptual framework of absorptive capacity for banking sector, and clarifies the main implication of absorptive capacity theory for the development of marketing and management, thereby providing sources for future research.